2006
DOI: 10.1029/2006jd007305
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparisons of trace gases profiles from the Odin/SMR and Aura/MLS limb sounders

Abstract: [1] This paper presents the intercomparison of O 3 , HNO 3 , ClO, N 2 O and CO profiles measured by the two spaceborne microwave instruments MLS (Microwave Limb Sounder) and SMR (Submillimetre Radiometer) on board the Aura and Odin satellites, respectively. We compared version 1.5 level 2 data from MLS with level 2 data produced by the French data processor version 222 and 225 and by the Swedish data processor version 2.0 for several days in September 2004 and in March 2005. For the five gases studied, an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 26 publications
(43 reference statements)
5
62
0
Order By: Relevance
“…The SMR CO measurements and data analysis methodology were described in detail by Dupuy et al (2004). Early qualitative comparisons with ACE-FTS were published by Jin et al (2005), whilst a detailed comparison of SMR/Odin with Aura/MLS can be found in Barret et al (2006).…”
Section: Smr/odinmentioning
confidence: 99%
See 2 more Smart Citations
“…The SMR CO measurements and data analysis methodology were described in detail by Dupuy et al (2004). Early qualitative comparisons with ACE-FTS were published by Jin et al (2005), whilst a detailed comparison of SMR/Odin with Aura/MLS can be found in Barret et al (2006).…”
Section: Smr/odinmentioning
confidence: 99%
“…Note that the upper limit altitude of the MOZAIC measurement is often close to, or at the same altitude, as the ACE-FTS lowest measured altitude. estimated at better than 25 ppbv in the stratosphere increasing up to 1-2 ppmv at ∼80 km (Barret et al, 2006). The SMR CO measurements and data analysis methodology were described in detail by Dupuy et al (2004).…”
Section: Smr/odinmentioning
confidence: 99%
See 1 more Smart Citation
“…The Aura-MLS ozone version 1.5 dataset was compared with numerous correlative datasets (including SAGE II, HALOE, POAM III and the previous data version (v2.1) of ACE-FTS O 3 ) in the early validation study of and with Odin/SMR (Bordeaux version 222 processor) by Barret et al (2006). An overall agreement of 5-10% was found throughout the stratosphere, with Aura-MLS biased high in the lower stratosphere but low in the upper stratosphere.…”
Section: Aura-mlsmentioning
confidence: 99%
“…Most of the measurements have been validated (e.g. Barret et al, 2006). The present study is based upon the retrievals of the 502.296-GHz N 2 O line measured by Odin/SMR using the Optimal Estimation Method (Rodgers, 2000 , 2006).…”
Section: Introductionmentioning
confidence: 99%